The Effectiveness of PowerPoint-Based Learning Media on Social Studies Learning Motivation - Paolin, Titin; Mustikarani, Wini; Widyanti, Triani (SAHUR Journal, 2023)
Problems in the world of education at the time of the outbreak of COVID-19, which can cause students to experience obstacles in learning. The use of learning media using technology is closer to its use by students because, currently, various activities are closely related to technology. Learning with technology can be conveyed through various media or multimedia. The research approach uses quantitative research methods, such as the quasi-experimental design, and the research design uses a nonequivalent control group design. Then the purposeful or judgmental sampling technique. Research data collection techniques using tests identified through pretests and posttests and non-tests through observation, interviews, and documentation studies Data validation analysis techniques use validity tests, normality tests, homogeneity tests, hypothesis tests, and normalized gain tests. The results of the study showed that (1) there was no significant difference in pre-test results between the experimental class and the control class before learning began. (2) There is a significant difference in pre-test results between the experimental class and the control class before learning begins. (3) There is an increase in students' learning motivation when PowerPoint learning media is applied. The conclusion is that the learning PowerPoint medium plays a role in supporting students' learning motivation.